Analysis of Customer Feedback for an e-Commerce Application Based on Artificial Neural Networks - Sri Anita; Army, Widya Lelisa; Nugroho, Arif (APIC, 2025)
With the rise of the Internet, e-commerce platforms have become one of the primary shopping channels for consumers. Establishing an efficient and intelligent customer service system is a crucial challenge for these platforms. This research aims to analyze how the interactivity of e-commerce applications and customer feedback from online shopping experiences can influence consumer loyalty and the likelihood of repurchase. To evaluate customer loyalty, we utilize an artificial neural network, which is processed using the SPSS application. The findings indicate that the relationship between interactivity, consumer feedback, and loyalty has a confidence level of 85.4%. A relationship between variables is considered strong if the R-squared value is above 50%, while a value below 50% indicates a weaker relationship.